Portal versus systemic venous drainage of the pancreatic graft: the effect on glucose metabolism in pancreas and kidney transplant recipients - Havrdová, Terezia; Bouček, Petr; Jedináková, Teodora; Lipar, K; Kočík, Matěj; Skibová, Jelena; Saudek, František (Transplantation proceedings, 2014)
Two different methods of graft venous drainage are used in pancreas transplantation: portal (PVD) and systemic (SVD). PVD is considered to be more physiologic due to its similarity to venous outflow of the native pancreas. The aim of our study was to compare glucose metabolism in Type 1 diabetic recipients of kidney and pancreatic grafts with PVD versus SVD by intravenous glucose tolerance test (IVGTT). We examined 28 insulin-independent patients after simultaneous pancreas and kidney transplantation: 14 recipients with PVD of the pancreatic graft and 14 with SVD after a mean post-transplant period of 1 year. All recipients had stable good function of the kidney graft. Fasting glycemia, insulin levels, glycosylated hemoglobin (HbA1c), and standard IVGTT with coefficient of glucose assimilation (KG) calculation were assessed. Insulin sensitivity and production were evaluated using the homeostasis model assessment (homeostasis model assessment of insulin resistance [HOMA-IR], homeostasis model assessment of B-cell function [HOMA-B]). Total C-peptide and insulin secretions were calculated as areas under the curves (AUCs) from the serum levels during the IVGTT. PVD and SVD groups did not differ in age, body mass index (BMI) and duration of post-transplantation period (P ≥ .05). We did not find any significant difference in fasting glycemia, HbA1c, KG, HOMA-IR, parameters of C-peptide level, fasting insulin level, and response during IVGTT. HOMA-B and AUC of insulin level were higher in the SVD group (45.1 ± 35.1 versus 19.8 ± 15.5, P =.03 and 1075 ± 612 versus 1799 ± 954 mIU/L/60 minutes, P < .03, respectively). In the PVD group, 1 patient had an abnormal response to the glucose stimulus, 8 patients had an impaired glucose tolerance, and 5 patients had a normal glucose tolerance. In the SVD group, an abnormal response was present in none, impaired glucose tolerance in 4, and normal glucose tolerance in 10 recipients. Athough this was not a prospectively randomized trial, we conclude that the change of surgical technique from SVD to PVD did not lead to any substantial change in terms of glucose tolerance.
Keywords: homeostáza; Insulin; C-peptid; Glucose; diabetes mellitus 1. typu; Male; inzulin; transplantace slinivky břišní; glykovaný hemoglobin; vena portae; Homeostasis; Adult; Pancreas Transplantation; dospělí; glukosa; mužské pohlaví; B-Lymphocytes, Regulatory; lidé; ženské pohlaví; Glycated Hemoglobin; transplantace ledvin; Humans; Kidney Transplantation; C-Peptide; Glucose Tolerance Test; Diabetes Mellitus, Type 1; regulační B-lymfocyty; Portal Vein; Female; lidé středního věku; glukózový toleranční test; Middle Aged